(Dis)Connected. Energy Materialities of Isolated Sites in Mountain Areas - Marie Forget; Kilian Ayroles (Revue de Géographie Alpine)
Mountain territories have a special role in the energy transition, because of their sensitivity to climate change and for the natural resources they contain. The geographical configuration of isolated territories gives them a key role in the development of disconnected energy solutions, through autonomous and renewable ones. These sites enable the study of the solutions’ materiality and authorises questioning the place dependence and the socio-technical path based on electrical networks. This article aims at exploring the energy materialities in isolated mountain sites in the Alps. It questions the modalities of (de)connection as well as their motivations through a multiscalar approach, from the buildings, to high altitude hamlets, and to the integration of valleys. This analysis informs more broadly the materialities of isolation in the energy transition, creating catalytic spaces for innovation and experimentation of a transition based on a sober, efficient and decentralised energy model.